Family Characteristics Related to Family Support in Caring for Mental Disorder Patients - Farida, Farida; Livana, P. H. (Open access Macedonian journal of medical sciences, 2022)
Mental disorders currently experience a very significant increase, and every year in various parts of the world the number of people with mental disorders increases. The main symptoms or symptoms that are prominent in mental disorders are in the psychiatric elements, but the main causes may be in the body (somatogenic), in the social environment (sociogenic) or psychic (psychogenic). Usually there is no single cause, but several causes at the same time. which influence each other or happen together, then arises body or soul disorders. The research design using descriptive correlation study with the research subjects were the families of patients who took patients in the psychiatric hospital of Dr. H. Soewondo numbered 145 families taken using accidental sampling technique. Data were analyzed using chi-square test. The results of the study show that there was a relationship between age, sex, and education with family support in caring for Mental disorders (p value <0.005).